2019
DOI: 10.4102/phcfm.v11i1.2095
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning and satisfaction: A comparative study between hookah users and non-users

Abstract: BackgroundAlthough there has been an exponential growth in hookah use on a global scale, research within the context of South Africa is very limited. While hookah use is known internationally to be a health and addiction risk, the focus is on university students and not on families.AimThis study aims to compare the family functioning and family satisfaction among hookah users and non-users.SettingThis study was conducted in low or middle-high class socio-economic status areas of Cape Town, South Africa.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…These findings are consistent with previous findings locally and internationally. An SA study conducted by Roman et al [37] indicated that one-third (34%) of the participants indicated that they smoked the hookah pipe, for which the general age of onset was 16.5 years. The majority of the participants in the study by Roman et al [37] started smoking the hookah pipe between the ages of 13 and 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous findings locally and internationally. An SA study conducted by Roman et al [37] indicated that one-third (34%) of the participants indicated that they smoked the hookah pipe, for which the general age of onset was 16.5 years. The majority of the participants in the study by Roman et al [37] started smoking the hookah pipe between the ages of 13 and 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…An SA study conducted by Roman et al [37] indicated that one-third (34%) of the participants indicated that they smoked the hookah pipe, for which the general age of onset was 16.5 years. The majority of the participants in the study by Roman et al [37] started smoking the hookah pipe between the ages of 13 and 15 years. Internationally, the age of onset for hookah use was reported as 13 years, in a study by Perez et al [38] Regarding the attitudes towards tobacco use of hookah pipe users and non-users, both groups considered that smoking the hookah makes 'people look sexy and tough' .…”
Section: Discussionmentioning
confidence: 99%